Synergistic effects of hybrid fillers on the development of thermally conductive polyphenylene sulfide composites. Issue 5 (14th May 2012) - Leung, Siu Ning; Khan, Muhammad Omer; Chan, Ellen; Naguib, Hani E.; Dawson, Francis; Adinkrah, Vincent; Lakatos‐Hayward, Laszlo
Abstract The future of integrated circuits with three‐dimensional chip architecture hinges on the development of practical solutions for the management of excessive amounts of heat generation. This requires new polymer–matrix composites (PMCs), with good processibility, high effective thermal conductivity (keff), and low but tailored electrical conductivity (σ). This article explores the synergy of hybrid fillers: (i) hexagonal boron nitride (hBN) platelets with different sizes and shapes; (ii) hBN platelets with carbon‐based fillers promoting the keff of the polyphenylene sulfide (PPS) composites. It explores the promotion of interconnectivity among the fillers in the PPS matrix, leading to higher keff, by the uses of hybrid fillers. It discusses using carbon‐based fillers as secondary fillers to tailor the PMCs' σ. Finally, it presents the effects of hybrid fillers on the PMCs' coefficient of thermal expansion. © 2012 Wiley Periodicals, Inc. J. Appl. Polym. Sci., 2013